A bibliometric analysis of research hotspots and trends in transcranial magnetic stimulation and Alzheimer’s disease - Xu, Dingwen; Feng, Yang; Lu, Zhihua; Ma, Ruijia; Zhang, Weicai; Mou, Zhen; Zhang, Lingling; Tang, Xiufeng; Zhao, Zhenxiong; Zheng, Zhencang (Frontiers in Aging Neuroscience, 2025)
BackgroundResearch regarding Transcranial Magnetic Stimulation (TMS) and Alzheimer’s disease (AD) has been increasing; however, no bibliometric analysis has yet been conducted in this domain. This study employs bibliometric methods to identify research trends and hotspots concerning AD and TMS.MethodsWe conducted a search in the Web of Science Core Database for articles related to AD and TMS from January 1, 2014, to October 22, 2024. After stringent selection, we performed bibliometric analysis using Excel, VOSviewer, CiteSpace and CoreMine.ResultsThe number of articles pertaining to AD and TMS has increased annually, with a notable surge post-2020. The three leading countries in publication volume are China, the United States, and Italy. The top institutions contributing to this field include Harvard Medical School, the University of Toronto, and the University of Brescia. The author with the highest publication output is Giacomo Koch. The journal with the most publications is the Journal of Alzheimer’s disease. The 10 most frequently occurring keywords are Alzheimer’s disease, Transcranial Magnetic Stimulation, mild cognitive impairment, dementia, memory, double-blind, repetitive transcranial magnetic stimulation, noninvasive brain stimulation, cognitive impairment, and plasticity. Text mining has revealed that the anatomical structure “brain” and the gene “Amyloid Precursor Protein (APP)” are significantly related to both AD and TMS, suggesting that TMS may offer a therapeutic avenue for AD by modulating the activity of APP.ConclusionOur article employs bibliometric methods to unveil trends in research related to AD and TMS, including collaborations among countries, regions, and authors, as well as key research hotspots. We provide objective data that serves as a reference for scientific research and clinical work concerning AD and TMS.